Monitoring Ancient Buildings: Real Deployment of an IoT System Enhanced by UAVs and Virtual Reality - Manlio Bacco; Paolo Barsocchi; Pietro Cassara; Danila Germanese; Alberto Gotta; Giuseppe Riccardo Leone; Davide Moroni; Maria Antonietta Pascali; Marco Tampucci (IEEE Access, 2020)
The historical buildings of a nation are the tangible signs of its history and culture. Their preservation deserves considerable attention, being of primary importance from a historical, cultural, and economic point of view. Having a scalable and reliable monitoring system plays an important role in the Structural Health Monitoring (SHM): therefore, this paper proposes an Internet of Things (IoT) architecture for a remote monitoring system that is able to integrate, through the Virtual Reality (VR) paradigm, the environmental and mechanical data acquired by a wireless sensor network set on three ancient buildings with the images and context information acquired by an Unmanned Aerial Vehicle UAV. Moreover, the information provided by the UAV allows to promptly inspect the critical structural damage, such as the patterns of cracks in the structural components of the building being monitored. Our approach opens new scenarios to support SHM activities, because an operator can interact with real-time data retrieved from a Wireless Sensor Network (WSN) by means of the VR environment.